ANALISIS INTERAKSI OBAT PADA PASIEN COVID-19 DENGAN PENYAKIT ASMA DI INSTALASI RAWAT INAP RSD GUNUNG JATI - lestari, trisna; Nuiah, Lilis Kholida; Junaedi, Aan (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Covid-19 with treatment of asthma must be considered. Because comorbid patients experience polypharmacy, this study aims to determine patient profiles, drug interactions based on mechanism,severity and significance of the use of Covid-19 drugs with asthma comorbidities at the inpatient installation of RSD Gunung Jati Cirebon.This study is a non eksperimental study with retrospective data collection, namely medical record data of patients with confirmed Covid-19 with comorbid asthma. Sampling using total sampling technique as many as 51 medical records. The study was conducted from November 2022 ti July 2023. Determination of drug interactions using the drugs.com application. Descriptive statistical data analysis in the form of percentages and tables. Based on the result of a study of Covid-19 patients with comorbid asthma, the age group was dominated by the group of 46-55 years (31%) and the gender of 32 patients (62%) was female. There were 14 potential drug interaction events from 51 patienst with a pharmacodynamic mechanism of action in 31 cases (91,18%) and pharmacokinetics in 3 cases (8,82%). Based on the level of severity, namely 7 cases (20,59%) for major interactions, 21 cases (61,76%) for moderate, 6 cases (17,65%) for minor. Covid-19 drug interactions with asthma comorbidities are mostly pharmacodynamic mechanism and moderate in severity.